THE USE OF INFORMATION TECHNOLOGIES IS IN TEACHING OF ECONOMIC DISCIPLINES (Journal of Information Technologies in Education (ITE), 2010)
The essence of informational technology, informational resources and distance technologies are analyzed. The use of the following forms are determined as he high mobile level, engaged a large number of students, and belonged to the one of the most effective and perspective systems of specialist preparation.
Keywords: distance education; informational resources; informational technologies